Adding value to the intelligence community: what role for expert external advice?. Issue 6 (18th September 2020) - Dover, Robert
ABSTRACT: Reviews of intelligence failures have recommended greater use of external expertise in challenging intelligence community assessments. External contributions were expected to augment covert collection and to provide open-source challenge to analysts, rather than to directly contribute to decision support. The structural limitations of the scope and machinery of intelligence have limited the value agencies can extract from external experts. Creating an Open-Source Intelligence Agency of commensurate size to primary intelligence organisations would enable decision support to be provided to all government departments. It would widen the pool of sources and experts, providing for greater extraction of value from experts who are only partially included in this government activity.